Nonlinear modelling of quasi-resonant converters and their conducted EMI mitigation with sinusoidal frequency modulation - Deng, Junhong (2010)
In this research project, two aspects of undesirable waveform generation in dc-dc quasi-resonant converters ( QRC ) are analyzed. First is the nonlinear output responses due to the distortions in both switching frequency and supply voltage of the converter. Another is the conducted electromagnetic interference (EMI) emission in QRC.